Eco-Friendly Dyeing of Tencel Fabric by Using Natural Dye Extracted from Eucalyptus Leaves - Rehman, Faisal; Iqbal Hussain, Muhammad Ather; K Sadannavar, Mohmad Arslan; Yusra; Wei, Wang (Journal of Design and Textiles, 2023)
The usage of natural dyes as environmentally suitable dyeing methods has extended during the recent years. The prime focus of this research is on the extraction and purification of natural dyes from eucalyptus leaves. With its numerous applications, eucalyptus leaves are highly valued for their diverse application, particularly as a rich source of natural colours. Quercetin is the primary colouring component in eucalyptus leaves. It has been utilized as a food dye with strong antioxidant properties and as an antioxidant. The goal of this research is to dye Tencel fabric using eucalyptus leaf-derived natural dye. The dye was extracted by using an ultrasonic extraction technique. Different ratios of the two mordants copper sulfate and ferrous sulphate were applied. Dyeing was carried out with different temperatures and concentrations and the pre-mordanting method was used for mordanting. The dyed Tencel fabric displayed a good colour strength of (K/S = 4.72), CIELAB values, and good to excellent light fastness (5), wash (4-5), perspiration (4-5), and rubbing (dry and wet = 4-5) fastness properties.